VD_FINDINFO HC / 2013 / 752 vom 27. September 2013 - VD Tribunal cantonal (2013)
ACTION NOMINATIVE, AUTORISATION OU APPROBATIONEN GÉNÉRAL | 685b CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 312 al. 1 CPC (CH)